Dynamic breaking of a single gold bond - Ilya V. Pobelov; Kasper Primdal Lauritzen; Koji Yoshida; Anders Jensen; Gábor Mészáros; Karsten W. Jacobsen; Mikkel Strange; Thomas Wandlowski; Gemma C. Solomon (Nature Communications, 2017)
The force required to break a chemical bond is related both to the bond strength and the rate at which force is applied, however recent experiments on gold nanowires have challenged this view. Here, the authors perform breaking experiments on single gold-gold bonds and propose a solution to the apparent paradox.